2017
DOI: 10.1016/j.ijheh.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing patterns and determinants of latrine use in rural settings: A longitudinal study in Odisha, India

Abstract: IntroductionMonitoring of sanitation programs is often limited to sanitation access and coverage, with little emphasis on use of the facilities despite increasing evidence of widespread non-use.ObjectivesWe assessed patterns and determinants of individual latrine use over 12 months in a low- income rural study population that had recently received latrines as part of the Government of India’s Total Sanitation Campaign (TSC) in coastal Puri district in Odisha, India.Materials and methodsWe surveyed 1938 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 30 publications
7
62
1
Order By: Relevance
“…Unfortunately, only a handful of researchers have undertaken the task of analyzing and understanding user preferences, so the task remains large. In addition, most of the current approaches focus on one or two aspects of sanitation, such as usage or ownership, and cost or technical features [8], whereas some have a significant number of variables [6]. Moreover, researchers such as Simiyu [18] and Conradin [50] have evaluated technologies where they were already implemented, and as Nawab et al [13] suggested, it is possible and probably better to conduct the evaluation before the design and implementation based on user preferences, to improve and maybe ensure the acceptance of such systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, only a handful of researchers have undertaken the task of analyzing and understanding user preferences, so the task remains large. In addition, most of the current approaches focus on one or two aspects of sanitation, such as usage or ownership, and cost or technical features [8], whereas some have a significant number of variables [6]. Moreover, researchers such as Simiyu [18] and Conradin [50] have evaluated technologies where they were already implemented, and as Nawab et al [13] suggested, it is possible and probably better to conduct the evaluation before the design and implementation based on user preferences, to improve and maybe ensure the acceptance of such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, direct user and stakeholder participation, as well as empowerment by intermediate-level organizations, can provide an avenue to identify the needs of the community [57,64]. This implies that current and future interventions in the design, selection, development, and monitoring of technologies and the subsequent provision of sanitation services should involve community decision-makers who understand people's culture and behavior, to develop strategies with users as part of the process and to implement feasible, affordable, and user-accepted sanitation systems [6,7,9,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the reduction of mortality with sewage coverage and water supply coverage is 0.98 and 0.99, respectively, which denotes that they are intimately related ( Figure 2). As it has been inferred in other countries [30], the construction of water and sanitation supply systems supports the control and eradication of epidemic outbreaks; but in Mexico, implementers seem to be incentivized to prioritize the construction of sanitation or water supply systems over ensuring a sustainable behavior change and ensuring the use of the systems. If communities continue growing with this lag, the possibilities for development are scarce [27,31].…”
Section: Human Capitalmentioning
confidence: 99%
“…Access to sanitation is necessary to ensure water quality, but the provision of this service is more complicated, since it depends on many authority levels and it has a great impact on health and the environment [8]. It is important to mention that a sustainable sanitation system protects and promotes human health, is people-centered, responds to demand, does not contribute to environmental degradation or depletion of the resource base, is technically and institutionally appropriate, economically viable and socially acceptable, and it should have a high degree of As it has been inferred in other countries [30], the construction of water and sanitation supply systems supports the control and eradication of epidemic outbreaks; but in Mexico, implementers seem to be incentivized to prioritize the construction of sanitation or water supply systems over ensuring a sustainable behavior change and ensuring the use of the systems. If communities continue growing with this lag, the possibilities for development are scarce [27,31].…”
Section: Human Capitalmentioning
confidence: 99%
“…8 Recent evidence examining latrine use has found that access to a latrine may not imply usage, especially when something else is preferred over the latrine. 9 Nevertheless, to take advantage of the greatest health benefits of these water and sanitation interventions, consistent and continued use is necessary for the largest impact on health. 8,10 …”
mentioning
confidence: 99%